PERANCANGAN KOMUNIKASI VSUAL BOOKLET PROMOSI PARIWISATA DANAU KEMBAR ALAHAN PANJANG - YANDRI OLGA PUTRA, Drs. Syafwandi, M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Twin Lakes is located on the causeway Padang - Muara Labuh, namely lake above and below lake. This beautiful tourist attraction located in Nagari Alahan Panjang, people outside the region are still many who are unaware of what kind of tourism and travel Twin Lakes and did not know of the villa. Office pariwasata only promotion that is not optimal. Hopefully, by the design of this booklet media can help create the information to the public and make people aware of the tourism outside the Twin Lakes area in Alahan Panjang. From the survey results and observations writers interested in making a media campaign in order to become a guide informative booklet which could be material to broaden the collection.The method used in the design of the booklet is to approach the analysis of SWOT (Strength, Weakness, Opportunity, Threat). Besides the main media simple booklet also explains the beauty and tourist information in Twin Lakes. In addition to major media booklet, is also supported by the supporting media, such as stickers, x banners, posters, shirts, mugs, brochures, calendars, and keychains which aims to promote tourism in Twin Lakes. The design of this booklet media is expected to provide information to the community, and can add insight to develop a media campaign and knowledge about Twin Lakes.Keywords: Travel, Twin Lakes, Promotion, Booklet.